Analisis Peran Guru Tidak Tetap (GTT) Sebagai Guru Kelas Dan Operator Sekolah Di Kecamatan Sanankulon - Andareka Murih Aditya Sari; Abdulkadir Rahardjanto (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: The increasing quality of education in Indonesia until now is inseparable from the role of non-government employees teacher. Non-government employees' teacher is referred to as non-permanent teachers (GTT) in addition to being educators who play roles as operators in improving the quality of education in schools. This study aims to describe the role of non-permanent teachers as classroom teachers and school operators including 1) the role of non-permanent teachers as classroom teachers 2) the role of non-permanent teachers as school operators 3) school principals' policy in facing the role of non-permanent teachers who have roles double as a classroom teacher and school operator. In this study, researchers used a descriptive qualitative approach. Data collection techniques using in-depth interviews, observation, and documentation. Test the validity of data by extending the time of attendance and source triangulation. The results of the study showed that 1) non-permanent teachers in carrying out their role as classroom teachers cannot run optimally because they are often left behind to carry out their duties as school operators who leave the class at any time. 2) non-permanent teachers in carrying out their roles as operators have multiple tasks, namely as diasporic operators and BOS operators. 3) Principal policies that appoint non-permanent teachers as class teachers and school operators have an impact on the learning process in the classroom.Keywords: Temporary Teacher, School Operator, Principal Policy Abstrak: Membaiknya kualitas pendidikan di Indonesia sampai dengan sekarang tidak terlepas dari peran guru non PNS. Guru non PNS disebut sebagai guru tidak tetap (GTT) selain sebagai pendidik berperan sebagai operator dalam meningkatkan mutu pendidikan di sekolah. Penelitian ini bertujuan untuk mendeskripsikan tentang peran guru tidak tetap sebagai guru kelas dan operator sekolah diantaranya: 1) peran guru tidak tetap sebagai guru kelas 2) peran guru tidak tetap sebagai operator sekolah 3) kebijakan kepala sekolah dalam menghadapi peran guru tidak tetap yang memiliki peran ganda sebagai guru kelas dan operator sekolah. Pada penelitian ini peneliti menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data menggunakan wawancara mendalam, observasi dan dokumentasi. Uji keabsahan data dengan memperpanjang waktu kehadiran dan triangulasi sumber. Hasil penelitian menunjukkan bahwa 1) guru tidak tetap dalam menjalankan peran sebagai guru kelas tidak dapat berjalan secara maksimal karena sering di tinggalkan untuk melaksanakan tugasnya sebagai operator sekolah yang sewaktu-waktu meninggalkan kelas. 2)guru tidak tetap dalam menjalankan peran sebagai operator memiliki tugas ganda yaitu sebagai operator dapodik dan operator BOS. 3) Kebijakan kepala sekolah yang mengangkat guru tidak tetap menjadi guru kelas dan operator sekolah berdampak terhadap proses pembelajaran di kelas.Kata kunci: Guru Tidak Tetap, Operator Sekolah, Kebijakan Kepala Sekolah